Strategi Evaluasi Program Praktikum Fisika Dasar - Erwin Erwin; I Permana; Muhammad Syaipul Hayat (Jurnal Penelitian Pembelajaran Fisika, 2018)
Lab work is one of the ways taken not only to clarify the subject that have been taught but also to coached students to apply scientific methods in solving problems. In order to ensure the quality of practical implementation requires accurate data-based information support, a gradual evaluation system is needed to help make the right decisions in every action throughout the program. The evaluation approach used is the CIPP (context, input, process, and product). Data collection is through interviews, questionnaires and direct observation, The data collected at each stage of the evaluation were analyzed qualitatively with the descriptions